Coxiella burnetii in ticks, livestock, pets and wildlife: A mini-review - Celina, Seyma S.; Cerný, Jirí (Frontiers in Veterinary Science, 2022)
Coxiella burnetii is a zoonotic bacterium with an obligatory intracellular lifestyle and has a worldwide distribution. C. burnetii is the causative agent of Q fever in humans and coxiellosis in animals. Since its discovery in 1935, it has been shown to infect a wide range of animal species including mammals, birds, reptiles, and arthropods. C. burnetii infection is of public and veterinary health and economic concern due to its potential for rapid spread and highly infectious nature. Livestock are the primary source of C. burnetii infection in most Q fever outbreaks which occurs mostly through inhalation of contaminated particles. Aside from livestock, many cases of Q fever linked to exposure to wildlife. Changes in the dynamics of human-wildlife interactions may lead to an increased potential risk of interspecies transmission and contribute to the emergence/re-emergence of Q fever. Although C. burnetii transmission is mainly airborne, ticks may act as vectors and play an important role in the natural cycle of transmission of coxiellosis among wild vertebrates and livestock. In this review, we aim to compile available information on vectors, domestic, and wild hosts of C. burnetii, and to highlight their potential role as bacterial reservoirs in the transmission of C. burnetii.